Design of an Adaptive Stair-Climbing Robot Based on Heterogeneous Dual-Core Intelligent Control Technology - Tang, Jialing; He, Xiaoying (International Journal of Advanced AI Applications, 2026)
With the deepening trend of societal aging, the demand for mobile robots in scenarios such as elderly assistance, disability aid, logistics, and rescue is growing. Navigating stairs in complex, unstructured environments has become a key challenge in robotics. Traditional wheeled, tracked, or legged robots suffer from weak adaptability, insufficient stability, or high cost. This paper designs an adaptive stair-climbing robot utilizing a heterogeneous dual-core control architecture built with an STM32H743 microcontroller and a Raspberry Pi 4B. It integrates multiple sensors including an RGB-D camera, an Inertial Measurement Unit (IMU), and encoders. The Raspberry Pi 4B serves as the upper-layer intelligent decision-making core, performing planning and decision-making through fuzzy logic and Model Predictive Control (MPC). The STM32H743 acts as the lower-layer real-time control core, achieving precise execution via PID control. The robot can adapt to stairs with slopes of 30°–45° and step heights of 150–200 mm made of different materials, maintaining a stability margin of no less than 20 mm during climbing. Compared to traditional tracked robots, the stability margin is improved by over 35%. The robot demonstrates good stability and robustness in various stair environments, providing an innovative technical approach for mobile robots in complex terrains.